Tree Species Effect on Litter Decomposition and Nutrient Release in Mediterranean Oak Forests Changes Over Time - Aponte, Cristina; García, Luis V.; Marañón, Teodoro (Ecosystems, 2012)
ree species can affect the decomposition process through the quality of their leaf fall and through the species-speciﬁc conditions that they generate in their environment. We compared the relative importance of these effects in a 2-year experiment. Litterbags containing leaf litter of the winter-deciduous Quercus canariensis, the evergreen Q. suber and mixed litter were incubated beneath distinct plant covers. We measured litter carbon loss, 9 macro- and micronutrients and 18 soil chemical, physical and biological parameters of the incubation environment. Tree species affected decay dynamics through their litter quality and, to a lesser extent, through the induced environmental conditions. The deciduous litter showed a faster initial decomposition but left a larger fraction of slow decomposable biomass compared with the perennial litter; in contrast the deciduous environment impeded early decomposition while promoting further carbon loss in the latter decay stages. The interaction of these effects led to a negative litter–environment interaction contradicting the home-ﬁeld advantage hypothesis. Leaf litter N, Ca and Mn as well as soil N, P and soil moisture were the best predictors for decomposition rates. Litter N and Ca exerted counteractive effects in early versus late decay stages; Mn was the best predictor for the decomposition limit value, that is, the fraction of slowly decomposable biomass at the later stage of decomposition; P and soil moisture showed a constant and positive relation with carbon loss. The deciduous oak litter had a higher initial nutrient content and released its nutrients faster and in a higher proportion than the perennial oak litter, signiﬁcantly increasing soil fertility beneath its canopy. Our ﬁndings provide further insights into the factors that control the early and late stages of the decomposition process and reveal potential mechanisms underlying tree species inﬂuence on litter decay rate, carbon accumulation and nutrient cycling.
Keywords: decomposition limit value; Lignin; litter chemistry; litterbag; Plant–soil interactions; Quercus; Soil fertility